Aedes aegypti microRNA, miR-2944b-5p interacts with 3'UTR of chikungunya virus and cellular target vps-13 to regulate viral replication. - Sunil Kumar Dubey; Jatin Shrinet; Sujatha Sunil (Public Library of Science (PLoS), 2019)
Background RNA interference is among the most important mechanisms that serve to restrict virus replication within mosquitoes, where microRNAs (miRNAs) are important in regulating viral replication and cellular functions. These miRNAs function by binding to complementary sequences mostly in the untranslated regions of the target. Chikungunya virus (CHIKV) genome consists of two open reading frames flanked by 5' and 3' untranslated regions on the two sides. A recent study from our laboratory has shown that Aedes miRNAs are regulated during CHIKV infection. The present study was undertaken to further understand the role of these miRNAs in CHIKV replication. Methods/findings We observe that miR-2944b-5p binds to the 3' untranslated region of CHIKV and the binding is abated when the binding sites are abolished. Loss-of-function studies of miR-2944b-5p using antagomirs, both in vitro and in vivo, reveal an increase in CHIKV viral replication, thereby directly implying a role of miR-2944b-5p in CHIKV replication. We further showed that the mitochondrial membrane potential of the mosquito cells is maintained by this miRNA during CHIKV replication, and cellular factor vps-13 plays a contributing role. Conclusions Our study has opened new avenues to understand vector-virus interactions and provides novel insights into CHIKV replication in Aedes aegypti. Furthermore, our study has shown miR-2944b-5p to be playing role, where one of its target vps-13 also contributes, in maintaining mitochondrial membrane potential in Aedes aegypti.